Urgensi Penanggulangan Over Capacity Lapas sebagai Upaya Pemenuhan Hak Bagi Narapidana - Humaira Afdini; Amad Sudiro (Syntax Corporation, 2023)
The type of research used by the author is normative juridical, namely Legal research carried out by examining library materials called Literature Law research. The author's consideration in using this type of research is to know, analyze, and explain the Urgency of Overcoming Prison Overcapacity as an Effort to Fulfill Rights for Prisoners. Efforts to overcome the Overcapacity of Prisons in Indonesia adhere to two concepts contained in the RKUHP which will be enacted in 2026, namely the Purpose of Punishment and Criminal Individualization. First, the purpose of punishment is directed to community protection, community protection (social idefence), socializing convicts by guidance, restoring and crushing a sense of settlement and guilt in convicts and creating a balance between society and convicts